Treatment of Liver Cancer: Role of the Traditional Mongolian Medicine. (14th February 2022) - Bao, Xiaomei; Chen, Lu; Liu, Yiman; Sheng, Hua; Wang, Kailong; Luo, Yanming; Qin, Tongling; Liu, Ying; Qiu, Yuling
Abstract : Liver cancer is an extraordinarily heterogeneous malignancy with relatively high mortality and increasing incidence rate among the so far identified cancers. Improvements in liver cancer therapy have been made in the past decades, but therapeutics against liver cancer are still limited. Traditional Mongolian Medicine, formed and developed by the Mongolian people to maintain health in the medical practice of fighting against diseases, has been recognized as one of the key components of the world healthcare system. Traditional Mongolian Medicine has been used to treat various malignancies, including liver cancer, for a long time in Asia and its advantages have become more and more apparent. Herein, this review made a comprehensive summary of Traditional Mongolian Medicine, including the ideas in the liver cancer treatment, sources of medicines or prescriptions, traditional applications, modern pharmacological research, chemical structure and mechanisms of several monomer compounds isolated from Traditional Mongolian Medicine, with a view to finding promising drugs against liver cancer and expanding the clinical application of Traditional Mongolian Medicine in liver cancer therapy.